Immune regulation of experimental myasthenia. Issue 7 (July 1980) - Fuchs, S; Bartfeld, D; Eshhar, Z; Feingold, C; Mochly-Rosen, D; Novick, D; Schwartz, M; Tarrab-Hazdai, R
Abstract : Experimental autoimmune myasthenia gravis (EAMG) is an appropriate model for studying the molecular origin, immunological mechanism and regulation of myasthenia gravis. Several approaches are being utilised for the regulation of the immune response to AChR and for immunosuppression of EAMG: Corticosteriods and azathioprine can suppress EAMG concomitantly with suppression of immune responses to AChR. High dose cyclophosphamide treatment in mice facilitates the onset of EAMG and results in a selective suppression of the humoral response to AChR whereas the cellular response is enhanced. Specific immunosuppression of EAMG is achieved by using a nonmyasthenic, denatured AChR preparation which cross reacts with the intact receptor. Various degradations and modifications of AChR are being performed in order to identify the smallest molecular entity responsible for the myasthenic activity of AChR. Studies on specific monoclonal antibodies, anti-idiotypes, and on the effect of measles virus on EAMG are being described and their possible significance in regulating myasthenia are being discussed.